CARCASS WEIGHT OF BROILER GIVEN COCONUT MILKY JUICE AND BROWN SUGAR WATER AS DRINGKING WATER - Tabita Naomi Ralahalu; C. Ch. E. Latupeirissa; Max A. Tukalpaly (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
To produce optimum carcass weight, broiler need an adequate ration which meet their nutrients requirement. This result in high feed cost which in turn increase cost of production. Therefore it is important to solve the problem by using non-conventional feedstuff such as agriculture by product or other ingredients. The aims of this study were : 1). To examine the effect of giving coconut milky juice and brown sugar water as drinking water on carcass weight and (2). To use by product of coconut milky juice as drinking water. Experimental design used was complete randomized design, with three treatments and five replications. Each replication consists of six chicken. The treatments were P0 (ration + plain water), P1 (ration + coconut milky juice (mature)) and P2 (ration + brown sugar water). Variables measured were: voluntary feed and drinking water intakes, carcass weight and percentage. Ration offered was commercial ration BR I produced by P.T Panca Patriot Prima Sidoarja. Chemical compositions of the ration were water content 12 %, minimum crude protein 21%, minimum crude lipid 6%, maximum crude fiber 5%, energy 3065 kcal/kg, ash 6,5%, calcium 0.9 -1.1%, phospor 0.7 - 0.9%, antibiotic bacitracin Methylene, Disalcylate, Coccodistat Monensin. 90 DOC broilers strain CP 707 were used. An adaptation period of 7 days allowed the animals to accustom to feed given and drinking water, and followed by 5 weeks measurement period. During the experiment the animals were fed twice daily at 07.00 and 16.00 h. The animal had free access to drinking water. The amount of drinking water and feed given was recorded daily. Drinking water and feed refusals were weighed every morning before the next feeding. Parameters measured were water and feed intakes, live and carcass weight, and carcass percentage. Drinking water and feed intakes were determined by subtracting water and feed refusal from water and feed offered. Slaughtered weight were determined by weighing live animals after 10 hours fasting. Carcass weight was determined by subtracting non carcass weight from slaughtered weight. Analyses of variance were done using the General Linear Model (GLM). Least squares means and standard error were produced. Main effects were detected using LSD. Voluntary intakes were 1805.69 g, 1799.14 g, and 1806.66 g for P0, P1 and P2 respectively. The result shows that the treatments does not affect voluntary intake significantly (P > 0.05). However, broilers drank more (P < 0.05) coconut milky juice (mature) (P1/10287.2 ml), than plain water (P0/9118.8 ml) or water contains brown sugar (P2/9081.8 ml). Slaughter and carcass weight of broilers are 1701.33 g,1849.40 g, 1847.27 g and 1263.87 g, 1386.00, 1379.90, for P0, P1 and P2 respectively. Statistical analysis show significant differences (P < 0.05) in slaughter and carcass weight among the treatments in which those parameters are higher for broilers received P1 and P2 than that of P0. Carcass percentage is the ratio of slaughter and carcass weight, which are 74.27%, 74.93 and 74.71 for P0, P1 and P2, respectively. No differences in carcass percentage were obtained (P > 0.05) among the treatments. In conclusion, the present study has shown that giving 1 % brown sugar in drinking water and coconut milky juice (mature) as drinking water has no significant effect on voluntary intake and carcass percentage. However, giving brown sugar water and coconut milky juice (mature) affect drinking water consumption, slaughter and carcass weight.